Cerebral Venous Sinus Thrombosis and Hydrocephalus in a Vegan Secondary to Acquired Hyperhomocystinaemia - W. D. D. Priyankara; A.V. I. Chandimal; F. G. Sivagnanam; E. M. Manoj (Case Reports in Critical Care)
Cerebral venous sinus thrombosis associated with acute hydrocephalus and periventricular leukoencephalopathy is a challenging combination, in a critically ill with deteriorating neurology. We report a case of a young man with acute onset neuropsychiatric manifestations, admitted to the intensive care unit. He was found to have widespread cerebral venous sinus thrombosis, hyperintensities in basal ganglia, and acute hydrocephalus in magnetic resonance imaging, necessitating cerebrospinal fluid diversion, by way of an external ventricular drain and therapeutic anticoagulation. He had otherwise normal routine biochemistry, except for macrocytosis, which prompted us to suspect acquired hyperhomocysteinemia secondary to cobalamin and folate deficiency, in the background of him being a vegan. Replacement of vitamin B12, folic acid, pyridoxine along with anticoagulation and control of intracranial pressure with external ventricular drain lead to dramatic improvement of his neurology. Therefore, high index of suspicion is crucial for a better outcome in otherwise irreversible neurological damage in acquired hyperhomocystinaemia.